2010
DOI: 10.1111/j.1600-0765.2010.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

The human periodontal ligament cell: a fibroblast-like cell acting as an immune cell

Abstract: Therefore, pharmacological treatment of periodontitis should aim to reduce the release of proinflammatory agents not only from classical inflammatory cells but also from periodontal ligament cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
128
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 37 publications
3
128
0
2
Order By: Relevance
“…Also, it is reasonable to suggest that periodontal ligament cells play a key role as promoters of periodontal inflammation through these mechanisms 9) . Since a recent study suggested that periodontal ligament cells may have important implications for the development of new therapeutic strategies to treat periodontitis 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is reasonable to suggest that periodontal ligament cells play a key role as promoters of periodontal inflammation through these mechanisms 9) . Since a recent study suggested that periodontal ligament cells may have important implications for the development of new therapeutic strategies to treat periodontitis 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Along with various other cell types of periodontium, hPdLCs may be involved in the host response to periodontitis [19]. hPdLCs respond to P. gingivalis or its components by initiating an inflammatory response, including the expression and production of proinflammatory cytokines and chemokines, as shown both at the mRNA and protein levels [20][22].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal ligament (PDL) links teeth to alveolar bone and participates in alveolar bone remodeling. PDL cells reside in PDL space, characterized by the production of collagen fibers and mineralized tissue (Jonsson et al, 2011). Pattern recognition receptors (PRRs) on the resident cells of the periodontium play an important role in the innate immune response by recognizing bacteria-derived factors and promoting the production of cytokines and chemokines, which are key mediators of inflammation and bone loss (Cochran, 2008;Di Benedetto et al, 2013).…”
mentioning
confidence: 99%